Respuesta :

If b=-4 then you would replace b with -4, however since it is already a negative the two negatives would cancel eachother out and make a positve, so it would be 4(2) which = 8.

To evaluate (-B)2 for A = 5, B = -4, and C = 2, all we need to do is substitute the value for B into the B in the expression. Doing so gives us: [-(-4)]2. Now, it is just a matter of multiplying. Here is the process:
[-(-4)]2 => [4]2 => 8
The answer to your query would be 8. Hope this helps and have a fantastic day!